Integrating multiple dimensions of ecological stability into a vulnerability framework. (9th December 2021) - Urrutia‐Cordero, Pablo; Langenheder, Silke; Striebel, Maren; Angeler, David G.; Bertilsson, Stefan; Eklöv, Peter; Hansson, Lars‐Anders; Kelpsiene, Egle; Laudon, Hjalmar; Lundgren, Maria; Parkefelt, Linda; Donohue, Ian; et al.
Abstract: Ecological stability encompasses multiple dimensions of functional and compositional responses to environmental change. Though no single stability dimension used in isolation can fully reflect the overall response to environmental change, a common vulnerability assessment that integrates simultaneously across multiple stability components is highly desirable for ecological risk assessment. We develop both functional and compositional counterparts of a novel, integrative metric of overall ecological vulnerability (OEV). We test the framework with data from a modularized experiment replicated in five lakes over two seasons, examining functional and compositional responses to both pulse and press disturbances across three trophic groups. OEV is measured as the area under the curve integrated over the entire observation period, with the curve delimiting the difference between the disturbance treatment and undisturbed parallel controls, expressed either as the log response ratio of biomass (functional OEV) or community dissimilarity index (compositional OEV). Both, functional and compositional OEV correlated negatively with functional and compositional 'resistance', 'temporal stability' and 'final/extent of recovery' following both pulse and press disturbances, though less so with 'resilience' following a pulse disturbance. We also found a positive correlation between functional and compositional OEV, which reveals the potential to also evaluate the intricate linkage between biodiversity and functional change. Our findings demonstrate that OEV comprises a robust framework to: (a) capture simultaneously multiple functional and compositional stability components, and (b) quantify the functional consequences of biodiversity change. Our results provide the basis for an overarching framework for quantifying the overall vulnerability of ecosystems to environmental change, opening new possibilities for ecological risk assessment and management. Synthesis . Ecological stability comprises multiple dimensions that together encapsulate how ecosystems respond to environmental change. Considering these multiple aspects of stability simultaneously often poses a problem in environmental assessments, which frequently require overarching indicators of risk or vulnerability. While an analysis of multiple dimensions allows for deeper exploration of mechanisms, here we develop and test a new univariate indicator that integrates stability aspects under a broad range of disturbance regimes. Using a modularized experiment in Swedish lakes, we show that this integrative measure captures multiple stability dimensions reflecting compositional and functional vulnerability and their relationships between them. Abstract : Ecological stability comprises multiple dimensions that together encapsulate how ecosystems respond to environmental change. Considering these multiple aspects of stability simultaneously often poses a problem in environmental assessments, which frequently require overarching indicators of risk or vulnerability. While an analysis of multiple dimensions allows for deeper exploration of mechanisms, here we develop and test a new univariate indicator that integrates stability aspects under a broad range of disturbance regimes. Using a modularized experiment in Swedish lakes, we show that this integrative measure captures multiple stability dimensions reflecting compositional and functional vulnerability and their relationships between them.